Understanding the complex interplay of victimization experiences, empathy and school climate in Tunisian schools - Chokri, Imed; Jarraya, Mohamed (Frontiers in Education, 2024)
Aim Our study aims to examine the interactions between empathy, victimization, and the school climate in Tunisian primary schools. Method In total, 312 school children (158 boys and 154 girls), with a mean age of 10.75 ± 1.32 years old participated voluntarily in the study. The students answered three scales that measure the School Climate, the Victimization, and the Empathy. Result The results indicate a predominantly positive perception of the school climate by the students, both for the overall score (2.67 ± 0.64) and the scores of the different components of the school climate (ranging from 2.61 to 2.86). Also, girls seemed to have a more positive perception of the overall school climate, displaying higher scores (2.86 ± 0.54) compared to boys' scores (2.45 ± 0.67). Moreover, other results showed positive and statistically significant correlations (p < 0.01) between the different dimensions of the school climate. Conclusion The findings highlight the importance of creating a safe and inclusive school environment where empathy is encouraged, and effective measures are in place to prevent and address victimization.